THE ROLE OF SOCIAL MEDIA IN SHAPING CLIMATE CHANGE (CC) AWARENESS AMONG ARAB UNIVERSITY STUDENTS - Abdellateef Alqawasmi; Sawsan Taha; Najeh Alsalhi; Hanan El-Gendi; Bushra Alakashee; Jehad Ali Bani Baker; Mustafa Hameed AL-Taei (Fonseca, Journal of Communication, 2024)
This paper delves into the largely unexplored area of changes in climate awareness among Arab university students, focusing on the influence of social media in shaping this awareness. The paper examines the intersectionality of demographic, academic, and socio-economic factors that shape students’ awareness of changes in climate. The paper provides new insights into the function of social media proficiency and education level in shaping Arab students’ understanding of Changes in climate. These insights carry significant implications for the development of strategies aimed at fostering Changes in climate awareness and promoting sustainable behaviors among Arab university students. The research demonstrates that university students have a strong understanding of changes in climate as a sustainability goal. Their perception is significantly influenced by social media platforms, highlighting their function in shaping climate awareness. A robust positive correlation between students’ Changes in climate awareness and their social media usage was found - increased usage is associated with heightened Changes in climate awareness.